2022
DOI: 10.1016/j.crmicr.2021.100091
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of pesticides and antibiotics among beneficial soil microbes recovered from contaminated rhizosphere of edible crops

Abstract: Highlights Soil bacterial isolates were recovered from contaminated rhizosphere regions. Majority of bacterial isolatesshowed multifarious plant growth promoting (PGP) activities. Bacterial isolates exhibited a varied level of pesticide tolerance. Sensitivity/resistance pattern among isolates was variable Pesticides tolerance and antibiotic resistance among soil isolates were variably correlated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 90 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…, Pseudomonas , Azotobacter and phosphate-solubilizing bacteria. 54 In profenofos-amended agricultural soils, Acinetobacter sp. and Comamonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Pseudomonas , Azotobacter and phosphate-solubilizing bacteria. 54 In profenofos-amended agricultural soils, Acinetobacter sp. and Comamonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Similar ability to tolerate a variety of pesticides has been documented in different soil isolates, viz., Pseudomonas, Azotobacter and phosphate-solubilizing bacteria. 54 In profenofosamended agricultural soils, Acinetobacter sp. and Comamonas sp.…”
Section: Isolation Pgp Features Pesticide Tolerance and Molecular Ide...mentioning
confidence: 99%
“…Several studies have discovered that endophytic bacteria are important in alleviating salt stress in a range of agricultural plants [ 16 , 17 ]. For instance, PGP endophytic bacterium Cronobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Saudi Arabia on the bacterium Bacillus megaterium isolated from root-nodules of Medicago sativa, the results showed that some attributes promote growth, such as indole acetic acid production and inorganic phosphate solubilization (Khalifa and Almalki, 2015). Besides that, three PSB species, Bacillus, Azotobacter, and Pseudomonas, showed a significant reduction in heavy metal uptake by corn plants due to increased P solubility and phytostabilization of heavy metals (Shahid and Khan, 2022).…”
Section: Phosphate Solubilizing Bacteria (Psb)mentioning
confidence: 99%